Clinical Severity and the Mental Health Treatment Gap Among Nursing Students: Findings From the Healthy Minds Study - Lisa M. Black Thomas (Nurse Educator, 2026)
Background: Nursing students report high rates of psychological distress, but how their use of mental health treatment varies with symptom severity is unclear. Purpose: To describe mental health symptom prevalence and treatment use among nursing students and examine the association between clinical severity and help-seeking. Methods: Secondary analysis of 2024 to 2025 Healthy Minds Study data from nursing students (N = 5817). Depression and anxiety were measured with the PHQ-9 and GAD-7; suicidality and past-year therapy were self-reported. χ 2 tests and odds ratios assessed associations. Results: Overall, 64.4% screened positive for ≥1 mental health problem, but only 33.3% reported past-year therapy. Help-seeking rose with severity (odds ratio, 1.76 for major depression to 2.87 for suicide attempt; all P < .001), yet more than 40% reporting a suicide attempt received no care. Conclusions: Clinical severity alone does not ensure treatment; proactive, profession-sensitive strategies are needed.